Case reportTreatment strategies for aorta-right ventricular fistula associated with aortic and/or mitral valve replacements: a case report with a review of the literature - Karapinar, Hekim; Kucukdurmaz, Zekeriya; Gumrukcuoglu, Hasan Ali; Kayancicek, Hidayet; Gul, Ibrahim; Yilmaz, Ahmet (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
We report a case of aorta-right ventricular fistula associated with aortic and mitral valve replacements. We considered it as a paravalvular leakage. Aorta-right ventricular fistula is a very rare variant of paravalvular leakage. We discuss the aetiology, diagnosis, and preventive and therapeutic options in the modern era.